Propagation of Theobroma cacao by Rooted Cuttings in Mini-Tunnels - Lucía Melissa Vásquez Zamora; Sofía Rengifo-Del Aguila; Juan Carlos Guerrero Abad; Geomar Vallejos Torres; Sixto Alfredo Imán Correa; Elías Torres Flores; Francisco Mesén Sequeira; Mike Anderson Corazon Guivin (Advances in Agriculture)
Cacao is an economically important crop that is currently planted in Asia, Africa, and America. Cuttings is a technique of vegetative propagation suitable for the conservation of selected desirable characteristics in cacao trees. The objective of this study was to evaluate the rooting of cacao cuttings in mini-tunnels with different doses of indole-3-butyric acid (IBA) to obtain a simple and viable vegetative propagation protocol. The experiment was carried out under a completely randomized design (CRD). Cuttings 5 to 7 cm long were collected from the middle area of cacao tree crowns and treated with doses of 0, 1000, 2000, and 3000 ppm of IBA; then they were placed in Jiffy© pellets and set to root in plastic-covered mini-tunnels with fog irrigation. The results indicate that treatments with 0 and 1000 ppm of IBA produced the highest values in survival (100%, both treatments) and rooting percentage (87.7 and 90.0%, respectively) as well as number and length of roots (4.3 roots-4.21 cm in length and 4.5 roots-5.32 cm in length, respectively); likewise, cuttings treated with 0 ppm rooted after 24–40 days, followed by doses of 1000 ppm (24–46 days). All rooted cuttings without IBA (0 ppm) achieved 100% acclimatization in nursery. In general, the best results were obtained without IBA application (Control 0 ppm) in all the parameters evaluated, similar to those obtained with the application of 1000 ppm IBA; these results indicate the success and efficiency of the vegetative propagation protocol proposed in this study.